Secondary palatoplasty in velopharingeal insufficiency closure using double opposing Z-plasty technique: Palatoplasti sekunder pada penutupan insufisien velofaring menggunakan teknik double opposing Z-plasty - Andi Tajrin; Faisal (Makassar Dental Journal, 2021)
Objective: The surgical management of cleft palate or velopharyngeal insufficiency is anatomical reconstruction of an intact structure for improvement of speech outcome while minimizing the incidence of oronasal fistula. Case: A 20 years old male came to the outpatient clinic in Hasanuddin University Dental Hospital with a chief complaint of speech problem. He have had lip dan palate surgery previously. Management: Secondary palatoplasty was performed using double opposing z-plasty techni-nique. Discussion: There was an optimal soft palate lengthening after surgery and speech outcome will evaluate regularly. Con-clusion: The treatment of secondary cleft palate using double opposing z-plasty provide adequate lengthening of soft palate in the patient.